A novel practical trocar placement technique for extraperitoneal laparoscopic and robotic-assisted laparoscopic radical prostatectomy in patients with lower midline abdominal incisions - Gözen, Ali Serdar; Akın, Yiğit; Akgul, Murat; Yazici, Cenk; Klein, Jan; Rassweiler, Jens (Journal of laparoendoscopic & advanced surgical techniques, 2014)
Objective: To describe a novel practical technique for trocar placement in extraperitoneal laparoscopic radical prostatectomy (eLRP) and robotic-assisted laparoscopic radical prostatectomy (eRALP) in patients who had lower midline abdominal incisions.Subjects and Methods: Between March 1999 and November 2013, 3080 LRPs were performed in our department. In total, 1745 eLRPs and 416 eRALPs were enrolled in the study. Group 1 consisted of 57 cases (45 eLRPs and 12 eRALPs) with median lower incision scars after previous abdominal surgery. Group 2 consisted of the same numbers of patients without previous surgeries after matched-pair analyses was performed according to body mass index, age, and operation style. Demographic, perioperative, and postoperative data were recorded. Additionally, we described our novel practical trocar replacement technique for extraperitoneal approach. Statistical analyses were performed.Results: Mean age was 65.6±6.2 years. Mean follow-up was 102.9±24.5 months. There were 12 eRALPs and 45 eLRPs in each group. Demographic, perioperative, and postoperative data were similar in the two groups except for trocar placement time. The trocar placement time was longer in Group 1 than in Group 2 (P<.001). In all patients with previous abdominal surgery with lower abdominal incision scars, we were able to establish trocar placement and correct access to the extraperitoneal space. Moreover, we had no conversions or complications in any patient.Conclusions: Our technique seems safe and practical for trocar placements for eLRP and eRALP in patients with lower abdominal incision scars.